A rare case of the recurrent surgery for cribriform-morular variant of papillary thyroid carcinoma - Enomoto, Keisuke (Int J Surg Case Rep, 2019)
INTRODUCTION: The cribriform-morular variant of papillary thyroid carcinoma (CMV-PTC) is an uncommon subtype of PTC, and it is associated with familial adenomatous polyposis (FAP). PRESENTATION OF CASE: We describe a 32-year-old female who presented recurrent CMV-PTC with FAP. Surgery performed after the recurrent disease resulted in left recurrent laryngeal nerve palsy due to formation of strong scar after initial operation. The histopathological examination revealed the recurrent CMV-PTC without thyroid capsular invasion in remnant thyroid tissue of berry ligament. In addition, the immunohistochemical analysis showed that β-Catenin was diffusely positive in both cytoplasm and nucleus in CMV-PTC tissue. CONCLUSION: Total thyroidectomy in CMV-PTC with FAP should be performed at initial surgery due to high recurrence.